2023
DOI: 10.1186/s12877-023-03762-z
|View full text |Cite|
|
Sign up to set email alerts
|

Nursing assistants’ knowledge, attitudes and training needs regarding urinary incontinence in nursing homes: a mixed-methods study

Abstract: Background Urinary incontinence is an increasingly common problem, especially among older people in nursing homes. Nursing assistants are the leading workforce in nursing homes, and their knowledge and attitudes regarding urinary incontinence have garnered considerable attention in the context of aging in China. However, most previous studies on this issue have focused on registered nurses. This study aimed to explore nursing assistants’ knowledge, attitudes and training needs with regard to ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The noteworthy and affirmative correlations identified among knowledge and attitude, knowledge and practice, and attitude and practice distinctly emphasize the inherent interconnectedness among these dimensions (10,11). Individuals with a more profound understanding of AF tend to demonstrate more favorable attitudes and adopt healthier practices.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The noteworthy and affirmative correlations identified among knowledge and attitude, knowledge and practice, and attitude and practice distinctly emphasize the inherent interconnectedness among these dimensions (10,11). Individuals with a more profound understanding of AF tend to demonstrate more favorable attitudes and adopt healthier practices.…”
Section: Discussionmentioning
confidence: 95%
“…The Knowledge, Attitude, and Practices (KAP) survey constitutes a research methodology aimed at evaluating the comprehension, perspectives, and behaviors of a particular group in relation to a specific subject matter, often applied in the realm of health literacy. This model hinges on the fundamental concept that knowledge exerts a positive influence on attitudes, subsequently shaping practices ( 10 , 11 ). In the realm of AF research, understanding the knowledge, attitudes, and associated practices of the general population in high-altitude regions regarding AF can facilitate the development of tailored health education and intervention strategies, aimed at enhancing early detection, management, and prevention of AF.…”
Section: Introductionmentioning
confidence: 99%
“…According to a crosssectional study of primary care health workers' income sources in the Democratic Republic of Congo, older nursing assistants especially have relatively low incomes and long working hours (Maini et al, 2017). With the development of society, the dilemma of the older nursing assistants did not improve, Liao et al confirmed that this situation is very common in developing countries (Liao et al, 2023). Aspects considered in late-career planning also included personal finances and meaningfulness of work (Brown et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge, attitude, and practice (KAP) questionnaire is a vital tool in healthcare for comprehensively assessing the knowledge, attitude, and behavior of a target population while also gauging their demand for and acceptance of relevant content [6][7][8]. The KAP model elucidates that individual behaviors are shaped by their knowledge and attitude, with the process of behavior change comprising three sequential stages: knowledge acquisition, attitude and belief formation, and the translation of these into practical behaviors [9].…”
Section: Introductionmentioning
confidence: 99%